Implications of Correspondence Inference Attribution Theory & Behavioral Jurisprudence Theory: Judge's Conciderations on Conscience - Cindy Debora Sinaga; Somawijaya Somawijaya; Agus Takariawan (SASI, 2022)
Introduction: This article analyzes the implications of the attribution correspondence inference theory and whether the urge of conscience as affect in the Defendant is the reason for the abolition of the sentence? also behavioral jurisprudence theory on judges' considerations, where it's often a discourse in Indonesia. It is necessary to explore the human values contained in Defendant.